Minoa lutea Schwingenschuss, 1954 (Lepidoptera: Geometridae: Larentiinae) recognized as bona species - Rajaei, Hossein; Gelbrecht, Jörg; Schulz, Nathalie; Hausmann, Axel (Zootaxa, 2021)
The species Minoa murinata (Scopoli, 1763) sensu lato is examined throughout its distribution range. Specimens from central Europe (Germany, Italy, France) are compared with those from Serbia, Croatia, Slovenia and newly collected specimens from eastern Turkey, Armenia, Georgia and Russia. The study is based on a combination of behavioural observations, morphological characters (size, wing coloration, structure of male and female genitalia) as well as genetic data (DNA barcoding). The taxon Minoa murinata var. monochroaria Herrich-Schäffer, 1848 is downgraded from subspecies rank to synonymy of M. murinata. Morphological study of the populations from eastern Turkey, Armenia, Georgia and Russia confirm the taxon Minoa murinata f./ssp. lutea Schwingenschuss, 1954 as a bona species. It is herewith upgraded from synonymy of M. murinata to species level. The results of DNA barcoding are discussed. Wing pattern, male and female genitalia of both species are illustrated.